About memristive effects in M-Ba(Sr)TiO3-M thin film structure - Buniatyan, V.V.; Dashtoyan, H. R.; Rustamyan, L. G.
Trapping/detrapping characteristics of thin film metal-ferroelectric-metal (m-f-m, Pt-BaxSr1-xTiO3-Pt) structure is considered assuming that the ferroelectric is in paraelectric phase and high concentration of oxygen vacancies (OV) in the interfacial regions of metal-ferroelectric contacts. It is assumed that these vacancies create electron trap levels in the band gap of the ferroelectric. At high electric fields (or at high temperatures) the oxygen vacancies are ionized due to detrapping of electrons via Pool-Frenkel emission which leads to change essentially the trap levels occupation function, f_t (E,t), and hence created a new non-compensated oxygen vacancies. These newly created charged vacancies, in turn, can change internal state, as well as m-f interfacial potentials, and thus may alter all processes of its based memristors. The nonlinear dependence of permittivity on applied electric field is taken into account too. Based on these assumptions analytical expression for the DC bias dependent traps level occupation function, f_t (E,t), its time dependence and ferroelectric material fundamental parameters dependencies are derived for the first time.
Keywords: Physics